U-571 - Copyright Collection (Library of Congress) (United States: Universal Pictures, 2000)
April 1942: Hitler's U-Boats are wreaking havoc in the Atlantic and destroying Allied shipping up and down the United State's east coast. Unable to crack the U-Boat radio codes, the U.S. struggles blindly against the German onslaught until the crew aboard the S-33, a vintage World War I submarine, is assigned a dangerous mission that, if successful, will have the power to turn the tide of battle permanently. Led by Commander Mike Dahlgren and Lt. Andrew Tyler, the S-33 crew is ordered to capture Enigma, the German's top-secret coding device.
Copyright: Universal City Studios, Inc. (employer for hire. PREV: Music prev. pub. Scripts prev. reg. 1999, PAu 2-421-533. NM: all other cinematographic material. DCR 1999; PUB 11Apr00; REG 24Apr00; PA981-484.
Summary taken from Baseline, 10/26/2000.
Sources used: copyright data sheet ; copyright data base ; Baseline, 10/26/2000.
Executive producer, Hal Lieberman ; director of photography, Oliver Wood ; editor, Wayne Wahrman ; music, orchestrations, Richard Marvin ; production designer, William Ladd Skinner.
Matthew McConaughey, Bill Paxton, Harvey Keitel, Jon Bon Jovi, David Keith, Thomas Kretschmann, Jake Weber.
Some German with some English subtitles.
Keywords: Thriller -- Feature; War -- Feature